IDENTIFIKASI ISI LAMBUNG IKAN KEPAET Osteochilus sp. ASAL PULAU BANGKA SEBAGAI DASAR PENGEMBANGAN DOMESTIKASI - Ulfa Dwinda Icas; Ahmad Fahrul Syarif; Eva Prasetiyono; Ardiansyah Kurniawan (Journal of Aquatropica Asia, 2019)
Kepaet fish is the one of local fish species found in rivers of Bangka Island. Kepaet fish has similarity with Cempedik from Belitung Island. The characteristic of this fish is a black spot near its tail and a silver scales color. This fish has potentially for aquaculture species, so its needs to to find out the type of natural feed. The purpose of this study aimed to describe the types of food in stomach contents of Kepaet fish and to expalined the types of feeding behaviour. The results showed that the main food of Kepaet fish is Synedra (Bacillariophyta) with IP value 57,56%, Nitzchia (Bacillariophyta) 20,16%, Closterium 11,45% and Aulacoseira 8% and complementary food is Gyrosigma, Rhizosolenia, Melosira, and Selenastrum with between IP Value 0,06%- 0,38%. Kepaet fish belongs to the herbivore fish group because has the relative length of the gut is 3,57.